Your daughters do not give to their sons and their daughters do not take for your sons (Ezra 9,12): intermarriage in Ezra 9-10 and in the pre-Maccabean Dead Sea Scrolls ; Teil 2 - Lange, Armin (Biblische Notizen, 2008)
Ancient Jewish literature in general and the pre-Maccabean literature from the Qumran library in particular allow for a better understanding of Ezra’s marriage reforms and their interpretation by the final stage of the book of Ezra / Nehemiah. Ezra’s measure of enforced mass divorce is unique in Second Temple Judaism which argues for its historicity. Ezra’s marriage reforms were probably motivated by a democratization of priestly intermarriage prohibitions. In light of the (enforced) Hellenistic acculturation of Ptolemaic Yehud, the final redaction of the book of Ezra Nehemiah reads Ezra’s marriage reform as a fight for the preservation of the religious and cultural identity of Judaism.